Effect of combination therapy of ruthenium polypyridyl complex, [Ru(dppz)2(PIP)]2+ and parp inhibitors against several cancer cell lines - Yusoh, Nur Aininie (2020)
Ruthenium polypyridyl complexes (RPCs) have been clinically studied as promising anticancer agents in the last decades. The RPC, [Ru(dppz)2(PIP)]2+ or RuPIP where dppz = dipyrido[3,2-a:2’,3’-c]phenazine and PIP = 2-(pheny)- imidazo[4,5-f][1,10]phenantroline has demonstrated anticancer properties where it was shown to stall DNA replication fork progression resulting in the initiation of DNA damage response (DDR) signaling which further lead to the inhibition of cell proliferation through G1/S-mediated cell cycle arrest. This has prompted us to study the rational combination of RuPIP alongside DDR inhibitors, particularly the inhibitors of poly (ADP-ribose) polymerase (PARP) to achieve synergistic effect in cancer cells. This is to enhance the therapeutic response to RuPIP in cancer cells while reducing the impact on normal cells. The cytotoxic effect of RuPIP and PARP inhibitors as single agents on several cancer cell lines (A549, MCF7, MDA-MB-231 and T24) were determined using MTT assay. RuPIP showed time-dependent reduction in the IC50 values meanwhile, both PARP inhibitors showed IC50 > 100 μM. All compounds showed IC50 > 100 μM on the normal NHDF cells. Drug combination study was carried out based on Chou and Talalay combination index (CI) method in which CI values were determined using Calcusyn and Compusyn software. Synergy (CI < 1) was observed with majority of RuPIP-olaparib combinations meanwhile, RuPIP-NU1025 resulted in a range of combination indices, ranging from synergism to antagonism. Importantly, the viability of normal cells observed for any combination tested was > 70%. Based on the average CI values, the synergistic combination (CI = 0.87) of 25 μM RuPIP alongside 25 μM NU1025 or 5 μM olaparib were chosen for further experiments. Cells ability to survive post-treatment and form colonies was investigated using clonogenic survival assay with single-agent treatments showed survival fractions (S.F) > 75%. Interestingly, combination treatments reduced cell survival with RuPIP-olaparib (S.F. < 2%) showed lower survival than RuPIP-NU1025 (S.F. < 57%). Besides, treatments with 25 μM RuPIP sensitize cells to olaparib where 60-fold reduction in IC50 value of olaparib was obtained for MCF7 (0.08 vs 4.75 μM) and 300-fold reduction was observed in MDA-MB-231 cells (0.06 vs 23.39 μM). Next, cell migration ability was investigated using cell scratch assay which revealed that RuPIP-olaparib combination significantly (P < 0.001) reduced cell migration with 40% reduction in wound closure was observed compared to control. The flow cytometric analysis on cell cycle distribution revealed that the combination treatment resulted in enhanced cell cycle arrest at G1/S phase in A549 cells (17.1% increase compared to control). Whereas both MCF7 and MDA-MB-231 cells were arrested at G2/M phase (19.7% and 20.4% increase compared to control, respectively). Subsequently, Annexin V-FITC assay showed that the combination treatment significantly (P < 0.001) increased the percentage of apoptotic cells with 25%, 30% and 31% increase compared to control in A549, MCF7 and MDA-MB-231 cells, respectively. These resultant cell deaths are associated with significant (P < 0.001) increase in the accumulation of double-strand breaks (DBSs) DNA damage with 45% increase in the percentage of cells with γH2AX foci compared to control. These findings established that RuPIP showed synergy with PARP inhibitors in several cancer cell lines with reduced impact on normal cells.